2018
DOI: 10.13168/agg.2018.0026
|View full text |Cite
|
Sign up to set email alerts
|

Development mechanism of mining-induced ground fissure for shallow burial coal seam in the mountains area of southwestern China: a case study

Abstract: Mining-induced ground fissure (MIGF) contributes to vegetation deterioration, landslides and other natural hazards. The study is an attempt to reveal the development type, dynamic development process, and formation mechanism of MIGF for MIGF-induced natural hazard prevention of shallow burial coal seam mining. A novel approach including in situ measurement, theoretical analysis, and numerical simulation was implemented. There are two typical types of fissures, namely sliding-type ground fissures and stepped-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…3 mm/m. A statistical relationship between the value and size of the deformations has been reported [20]. This also indicates a number of important factors determining the formation of linear deformations (fissures).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…3 mm/m. A statistical relationship between the value and size of the deformations has been reported [20]. This also indicates a number of important factors determining the formation of linear deformations (fissures).…”
Section: Introductionmentioning
confidence: 74%
“…30 to 450 m. Grabens are another form of deformations that are observed less frequently but pose a greater threat to buildings. The works by Zhu [20] and Kang [21] indicated that they occur in mountain terrains or at least steep slopes. This leads to the following questions: Is it the case that the only factor conductive to the occurrence of discontinuous linear deformations are faults characterized by a throw of several dozen and more meters?…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have also been reports of LDGD in Chinese hard coal mining, with two types of fissures in mountainous areas: slide-type on the slopes, and step-type in valleys [5]. The relationship between the LDGD fissure width and the horizontal strain value was also shown (Fig.…”
Section: State Of Knowledgementioning
confidence: 82%
“…The relationship between the ground fissure width and the horizontal strain value[5].thickness of the younger layers (above the Carboniferous) is about 200 m on the southern side and about 250 m on the northern side of Fault II. They are built of a thin quaternary layer and a thick tertiary layer.…”
mentioning
confidence: 95%
“…is system was defined in terms of the structure, motion, and fissure distribution of the key strata and aquifuge [10][11][12]. Yu et al studied the formation mechanism of mining-induced fissures in shallow coal seam mines and proposed preliminary control techniques [13,14]. In addition, other scholars in this field have carried out research on strata movement, mining subsidence, ecological restoration, etc.…”
Section: Introductionmentioning
confidence: 99%